Análisis de la recaudación tributaria de los ingresos permanentes en el Presupuesto General del Estado. Periodo 2016-2020 - Oña Cando, Jenny Xiomara (2021)
Fiscal policy is the fundamental instrument to be able to promote the economic development of the country. The General Budget of the State of Ecuador is made up of Permanent Income that constitutes a very important item, since tax collection from ancient times has been one of the ways to ensure the satisfaction of citizens' needs, such as health, education, security, among the most important. From there, the present investigation was raised with the objective of analyzing the behavior of permanent income in the General State Budget during the period 2016-2020. The methodology used is related to descriptive, documentary, bibliographic and correlational research; with a mixed approach, and interviews with specialists in tax matters were applied. The main results were that an annual increase in collection was evidenced with the exception of 2019 and 2020, since it is important to mention in the first year there were protests that paralyzed trade for a few days, and in 2020 these decreased as a result of the crisis caused by COVID-19, reduce all economic activity in the country, significantly affecting tax collection that will generate the largest contribution to the PGE……..